A Case-Control Study On The Effect Of Alcoholism On Saliva - DEEPTHI.K; DR.K.B. LALIYTHA (International Journal of Pharma and Bio Sciences, 2015)
Saliva is essential for the maintenance of oral health. Alcohol consumption produces peripheral autonomic neuropathy that causes disordered salivary metabolism and secretion and may even lead to salivary gland enlargement. Histologically, an increased intracytoplasmic zymogen granules is believed to be the etiology. To assess the unstimulated whole saliva in alcoholic patients. The objective of the present study was to evaluate the salivary flow rate in alcoholic and non alcoholic individuals to evaluate the salivary pH in alcoholic and non alcoholic individuals. To compare saliva in alcoholic and non alcoholic individuals. The study was conducted during the period of November 2014 to May 2015. The study comprised of 20 males of age between 30-50 years which included 10 alcoholic and 10 non-alcoholic individuals. The whole saliva flow rate and pH and DMFT index was determined. The mean salivary flow rate in case was 1.620 and in control was 1.700. The mean pH was 5.800 in case and 6.500 in control. Salivary pH was statistically significant between case and control. The mean DMFT score in case was 3.40 in case and 1.70 in control. The Saliva flow rate and DMFT index was not statistically significant between case and control subjects. To conclude alcohol consumption reduced the salivary pH, perhaps will increase DMFT index at a later stage. Future research studies with larger sample size may aid in better understanding of the concept.